Intervensi sport effectiveness terhadap kualitas hidup dan fungsi kardiovaskuler pada anak - Etik Pratiwi; Giri Susilo Adi (STIKes Surya Global Yogyakarta, 2020)
Sports is the most important part of activities in children and can improve physical fitness for the children. Respondents in this study are children who participate in sports programs in a sports club, especially swimming and running from the Special Region of Yogyakarta in February-March 2020. This study aims to determine the relationship between Sport effectiveness activities with quality of life and cardiovascular function in children. The method used was quantitative with cross-sectional correlation description design. Data collection techniques namely by distributing questionnaires specifically quality of life and measuring cardiovascular function using the Vo2Max beep test. Data were collected using a purposive method, with a total number of respondents who followed were 76 children aged 5-14 years. The number of male children were 35 children (46.1%) and women were 41 children (53.9%). The results of this study indicated that there was a relationship between the intervention